New Developed Data Treatments for the Characteristic Linear Array Ayah 5SX1-T-1D-CFI Analyser Segment Response Profile & Generalization - M.A. Shakir, Issam; K. Hammood, Mohammad (Iraqi Journal of Science, 2026)
Derivative spectrophotometry is one of the analytical chemistry techniques usedin the analysis and determination of chemicals and pharmaceuticals. This method ischaracterized by simplicity, sensitivity and speed. Derivative of Spectra conductedin several ways, including optical, electronic and mathematical. This operationusually be done within spectrophotometer. The paper is based on form of a newprogram. The program construction is written in Visual Basic language withinMicrosoft Excel. The program is able to transform the first, second, third and fourthderivatives of data and the return of these derivatives to zero order (normal plot).The program was applied on experimental (trial) and reals values of sulphatedetermination in the form of barium sulphate by a Linear Array Ayah 5SX1-T-1DCFI Analyser. The data was collected through an Array M3500A 6.5Digit DigitalMultimeter linked between the spectrometer and computer.